Inclusive Development as an Initiative to Alleviate the Social Exclusion of Urban Communities (Study on Street Vendors in Tedis Beach, Kupang City) - Selviana Selan; Resta Tasuib; Lasarus Jehamat; Hotlif A. Nope; Helga M. Evarista Gero; Christine E. Meka (Jurnal Pluralis, 2024)
This research discusses the role of inclusive development in reducing social exclusion, with a case study of street vendors in Tedis Beach, Kupang City. Inclusive development is an approach that emphasizes equal opportunities for all groups of society, especially the marginalized. This research uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results showed that street vendors in Tedis Beach face various challenges, such as limited access to business space and capital. However, the government has implemented supportive policies, including providing basic facilities and participation in development. In addition, the inclusive development approach creates opportunities for street vendors through economic empowerment and recognition of their contribution to the local economy. This research concludes that inclusive development positively reduces social exclusion by empowering street vendors, improving access to resources, and integrating them into urban planning. Recommendations are given to enhance regulations that support and ensure street vendors' participation in every development stage.